The phenomenon of Jihad: Historical Transformation and Modern Interpretation - Askhatuly, Zhalgas; Kabylova, Aina; Shamakhay, Saira; Myrzabekov, Muratbek; Kalemshariv, Balzhan (Journal of Al-Tamaddun, 2024)
The article seeks to differentiate the religious concept of jihad from its modern politicized interpretation to reduce Islamophobia. A historical review of modern Islamic values and principles is carried out. To confirm the hypothesis put forward, the author uses reliable information from the Holy Quran and hadith. The classical views of the Muslim scholars Ibn Qasir and Abu Jafar al-Tabari, who defended the religion of Islam from various misconceptions, are also presented as sources. The author conducted an etymological and hermeneutic analysis of the theory of “armed jihad” and religious concepts distorted for various political reasons. The features of the impact of the microenvironment and individual factors affecting the radicalization of a person are determined. At the same time, the author widely informs about the comprehensive work and measures taken to prevent religious extremism and terrorism in Kazakhstan. The reasons for the spread of radical religious ideology in Kazakhstan are presented in three stages, taking into account Kazakhstan’s experience in combating them.